2014
DOI: 10.1007/s00228-014-1782-y
|View full text |Cite
|
Sign up to set email alerts
|

A pilot randomized trial of pentoxifylline for the reduction of periprocedural myocardial injury in patients undergoing elective percutaneous coronary intervention

Abstract: This study could not support the pretreatment with pentoxifylline in the prevention of PMI in patients undergoing elective PCI. However, the trend was toward the potential benefit of pentoxifylline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In our recently published trial, a loading dose of 1200 mg pentoxifylline before elective PCI could not lead to a significant result. In this study, CK‐MB elevation was seen in 4.8% of intervention and 11.4% of control group ( P =.435) as well as the rise of troponin‐I was recognized in 6.8% of control group and in none of the intervention group ( P =.242) . Moreover, in one randomized trial, infusion of 3‐gram vitamin C within 6 hours before elective PCI significantly reduced PMI in vitamin C group as follows: CK‐MB, 4.2% vs 8.6%; P =.035 and troponin‐I, 10.9% vs 18.4%; P =.016 …”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In our recently published trial, a loading dose of 1200 mg pentoxifylline before elective PCI could not lead to a significant result. In this study, CK‐MB elevation was seen in 4.8% of intervention and 11.4% of control group ( P =.435) as well as the rise of troponin‐I was recognized in 6.8% of control group and in none of the intervention group ( P =.242) . Moreover, in one randomized trial, infusion of 3‐gram vitamin C within 6 hours before elective PCI significantly reduced PMI in vitamin C group as follows: CK‐MB, 4.2% vs 8.6%; P =.035 and troponin‐I, 10.9% vs 18.4%; P =.016 …”
Section: Discussionmentioning
confidence: 55%
“…In this study, CK-MB elevation was seen in 4.8% of intervention and 11.4% of control group (P=.435) as well as the rise of troponin-I was recognized in 6.8% of control group and in none of the intervention group (P=.242). 23 Moreover, in one randomized trial, infusion of 3-gram vitamin C within 6 hours before elective PCI significantly reduced PMI in vitamin C group as follows: CK-MB, 4.2% vs 8.6%; P=.035 and troponin-I, 10.9% vs 18.4%; P=.016. 24 To the best of our knowledge, there is no study investigated the cardioprotective role of CoQ10 following elective PCI.…”
Section: Discussionmentioning
confidence: 94%
“…We calculated the number of subjects needed for the study to be 98 (49 in each group) based on previous works with pentoxifylline and inflammatory responses in patients with coronary artery disease. 29,30 Descriptive statistics for the study population were evaluated by mean ± standard deviation. To compare the quantitative variables between the groups, chi-square and Fisher's exact tests were used.…”
Section: Discussionmentioning
confidence: 99%
“…In that randomized, controlled trial, 1200 mg of pentoxifylline before elective PCI did not result in a significant difference between the studied groups. 30…”
Section: Prognostic Value Of Cardiac Troponins Level In Stemi Patientsmentioning
confidence: 99%
“…25,26 In the first trial, a loading dose of 1200 mg pentoxifylline before elective PCI in 85 patients could not lead to a significant result. 25 The second trial among 100 patients showed that 300 mg coenzyme Q10 12 hours before elective PCI could not reduce PMI. However, it significantly decreased hs-CRP.…”
Section: Comparison With Other Trialsmentioning
confidence: 99%